Book review: Tsygankov, A. P., & Tsygankov, P. A. (2024). Globality and Originality. Russian Idea and World Theory of the 21st Century. Moscow: Prospekt publ., 280 p. (In Russian) - Alexei D. Bogaturov (Vestnik RUDN. International Relations)
-